Evidence of a Uniform Muscle-Tendon Unit Adaptation in Healthy Elite Track and Field Jumpers: A Cross Sectional Investigation - Epro, Gaspar; Hunter, Steve; König, Matthias; Schade, Falk; Karamanidis, Kiros (Frontiers in Physiology, 2019)
Different adaptive responses to mechanical loading between muscle and tendon can lead to non-uniform biomechanical properties within the muscle-tendon unit. The current study aimed to analyse the mechanical properties of the triceps surae muscle-tendon unit in healthy male and female elite track and field jumpers in order to detect possible inter-limb differences and intra-limb non-uniformities in muscle and tendon adaptation. The triceps surae muscle strength and tendon stiffness were analysed in both limbs during maximal voluntary isometric plantar flexion contractions using synchronous dynamometry and ultrasonography in sixty-seven healthy young male (n = 35) and female (n = 32) elite international level track and field jumpers (high jump, long jump, triple jump, pole vault). Triceps surae muscle-tendon unit intra-limb uniformity was assessed using between limb symmetry indexes in the muscle strength and tendon stiffness. Independent from sex and jumping discipline the take-off leg showed a significantly higher (p < 0.05) triceps surae muscle strength and tendon stiffness, suggesting different habitual mechanical loading between legs. However, despite these inter-limb discrepancies no differences were detected in the symmetry indexes of muscle strength (5.9 ± 9.4 %) and tendon stiffness (8.1 ± 11.5 %). This was accompanied by a significant correlation between the symmetry indexes of muscle strength and tendon stiffness (r = 0.44; p < 0.01; n = 67). Thus, the current findings give evidence for a uniform muscle-tendon unit adaptation in healthy elite track and field jumpers, which can be reflected as a protective mechanism to maintain its integrity to meet the functional demand.